MENELUSURI LATAR BELAKANG KOLABORASI ANTARINSTANSI PEMERINTAH KOTA BOGOR DALAM PENYALURAN BANTUAN SOSIAL SAAT PANDEMI COVID19 - Hermawan, Lili; Kartakusumah, Berliana; Luthfie, Muhammad (Universitas Djuanda, 2021)
The purpose of this research is to comprehend the aspects of intergovernmental collaboration in Bogor City, as evidenced by the utilization of the SALUR Kota Bogor application. This study employs a qualitative descriptive approach, with the Mayor of Bogor and collaborators from the Department of Communication and Informatics, Department of Social Affairs, and Department of Population and Civil Registration as informants. These informants were interviewed, and the interview outcomes were analyzed alongside secondary data obtained from literature studies. The analysis yielded findings that the collaboration background was a shared understanding of the existence of inaccurate data regarding social aid recipients. Building synergy, unity, and the mayor's directive were motivating factors for collaboration. Another finding is that collaboration aims to foster social solidarity, social cohesion, and cultivate a service-oriented bureaucratic culture. Another objective is to ensure accountability for the social aid budget in the regional budget. Collaborators contributed to their respective roles effectively. From a leadership perspective, the Mayor of Bogor successfully facilitated effective collaboration among the three departments and transformed social aid issues into shared concerns. In managing social aid, the employed management reflects the characteristics of New Public Services (NPS), enabling effective collaboration. The collaboration policy to address the recipient data issue required significantly fewer inputs compared to the achieved outputs.